Superman. Red son [videorecording (Blu-Ray + DVD)] - Liu, Sam; Liu, Sam; Millar, Mark (Warner Bros. Entertainment, 2020)
When Kal-El's rocket lands in the Soviet Union, he is raised to fight for the ideals of the Communist Party, and becomes Russia's greatest protector, Superman.